Apakah Layanan Digital Memuaskan Konsumen: Studi Empirik pada Bank BCA - Wikarma, Gabrielle Sylviera; Siagian, Dergibson (Jurnal Manajemen, 2023)
The covid-19 pandemic reduces face-to-face customer service and forces banks to initiate digital-based banking services. Gradually the traditional activities of banks are switching to digital banking, and banks are starting to compete to create digital banking that is easily accessible to customers. That practice is now growing rapidly. However, the customer's response to this new approach is not fully understood. Therefore, the authors detect customers' responses in the form of customer satisfaction and use customer experience and ease of use of digital customer service tools as presumed determinants. Using judgmental sampling to prove this notion, the authors recruited 113 customers as respondents. Structural equation modelling with WarPLS reveals that customer experience has no significant effect on customer satisfaction, while ease of use has. This study suggests the direction for further research based on the conclusion.